The Experience of Social Pedagogues and Social Workers when Realising the Right of the Child to Participate in Children’s Day Care Centres - Raudeliūnaitė, Rita; Gudžinskienė, Vida (Socialinė teorija, empirija, politika ir praktika, 2024)
The objective of the study is to reveal the realities of the realisation of the right of the child to participate in children’s day care centres based on the experience of social pedagogues and social workers. Qualitative research was chosen for the study by using the method of semi-structured interview. 11 professionals, who work in children’s day care centres in different Lithuanian regions, participated in the study. The study identified the expression of the realisation of the right of the child to participate in children’s day care centres. The expression of the right of the child to participate in children’s day care centres is associated with a positive position of the professionals in the practice of the child’s right to participation, their cooperation with the child, their mutual cooperation, their cooperation with the child’s parents/guardians and other institutions when realising the right of the child to participation. The positive position of the professionals is expressed through the understanding of the importance of this right and inclination to realise it, the acknowledgement of the child as an active participant in decision-making, openness to the opinion of the child and nonsuppression of their opinion. The cooperation of the professionals with the child is expressed through the creation of the relationships, which are based on mutual trust, the informing of the child that his opinion is important, that he can express it and be heard, the provision of information to the child in a way that is understandable to him while empowering him to participate in decision-making, the listening to the child and his support, the taking into account the child’s opinion while responding to his best interests, the analysis of situations and the discussion of various solutions with the child in a way understandable to him, assistance when taking decisions related to him, the involvement of the child and the taking into account his needs and interests when planning and organising socio-educational activities, the encouragement of the child to assume his obligations and responsibilities. The cooperation of children’s day care centres professionals is expressed though their favourable and unified approach towards this right, their involvement in the realisation of this right and the sharing of the experience when realising this right. The cooperation with the child’s parents/guardians is expressed through the assistance to them in understanding the importance and expression of this right, their consulting and assistance while creating conditions for this right to be expressed at home. The cooperation with other institutions is expressed through the sharing of information and insights on the positive aspects of the realisation of this right and the discussion of arising difficulties and possibilities to overcome them.